Advancements in battery technologies and management systems for electric vehicles A mini-review - Shanmuganathan, Elengespwaran; Norazlianie, Sazali; Kettner, Maurice; Salim, Naqib; Ismayuzri, Ishak (Semarak Ilmu Publishing, 2025)
The rapid adoption of electric vehicles (EVs) has driven the need for efficient and practical charging solutions to enhance reliability and reduce range anxiety. While advancements in lithium-ion battery technology have improved energy storage capacity, charging time and battery degradation remain critical challenges. Fast charging significantly reduces charging duration, making EVs more practical for daily use, but it accelerates battery aging, reducing long-term performance and sustainability. Addressing this issue requires innovative charging strategies that optimize battery performance without compromising lifespan. This mini-review explores recent advancements in smart charging technologies for EVs, with a focus on predictive algorithms and adaptive control strategies that enhance both charging efficiency and battery longevity. The integration of machine learning-based models, real-time monitoring, and thermal management systems has demonstrated the potential to mitigate battery degradation while maintaining high charging speeds. Additionally, the role of simulation tools such as Simulink in evaluating various charging methodologies is discussed, highlighting their significance in optimizing charging protocols. The review also examines developments in direct current (DC) fast charging infrastructure, including technologies such as Tesla’s Superchargers and AVL’s advanced charging solutions, which aim to provide rapid and efficient charging while addressing thermal and electrochemical challenges. Furthermore, strategies for reducing energy losses and improving battery management through state-of-charge (SOC) and state-of-health (SOH) monitoring are analyzed. By reviewing recent literature and advancements in EV charging, this study provides insights into the challenges and future directions of fast-charging technologies. Ultimately, the findings emphasize the importance of balancing fast charging with long-term battery health to support the widespread adoption of EVs. This mini-review serves as a foundation for future research and development efforts in the field of sustainable and intelligent EV charging systems, offering valuable insights for researchers, industry professionals, and policymakers.